1992
DOI: 10.1116/1.578174
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency sputtering process of a polytetrafluoroethylene target and characterization of fluorocarbon polymer films

Abstract: Fluorocarbon polymer films have been deposited on glass, silicon, and carbon substrates by radio frequency (rf) sputtering of a polytetrafluoroethylene (PTFE) target in pure argon and Ar–C3F8 mixtures using either a conventional sputtering mode or a self-sustaining glow discharge mode. The substrates could be isolated from the plasma region by a grounded grid electrode. The deposition rate of films produced on glass and silicon substrates was measured as a function of the gas composition and total pressure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[2][3][4][5] Previous studies showed that a surface modification of PTFE by plasma treatment in vacuum could lead to an increase in the water contact angle (WCA) and a roughening of the samples. [6,7] This roughness can be associated to the etching [8][9][10][11] of the PTFE surface with, in certain cases, the possible incorporation of oxygen-containing polar groups into the surface. [12] At low pressure (approx.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Previous studies showed that a surface modification of PTFE by plasma treatment in vacuum could lead to an increase in the water contact angle (WCA) and a roughening of the samples. [6,7] This roughness can be associated to the etching [8][9][10][11] of the PTFE surface with, in certain cases, the possible incorporation of oxygen-containing polar groups into the surface. [12] At low pressure (approx.…”
Section: Introductionmentioning
confidence: 99%
“…After being first reported in the 1970s, the plasma sputter-deposited fluoropolymers have been shown to be useful as the dielectric films, water-repellent coatings, low friction coatings, and even optical coatings. The sputtering processes have been carried out both in the magnetron sputtering systems and in tubular-type plasma reactors, , using different working gases, including Ar, N 2 , He, and Ne. The addition of fluorocarbon gases, such as CF 4 13 and C 3 F 8 , to Ar for glow discharging has also been carried out to enhance the deposition rate and to improve the fluorine content in the deposited films. An Argon ion beam has also been used for the sputtering deposition of fluoropolymer films .…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the deposited fluoropolymer films by multiple techniques is thus of great importance. A number of characterization techniques, such as Fourier transform infrared (FTIR) spectroscopy, , X-ray photoelectron spectroscopy (XPS), and Rutherford backscattering spectroscopy (RBS), have been employed for the surface analysis of the sputter-deposited fluoropolymers. Characterization of the deposited fluoropolymer films with molecular-specific techniques is essential to the elucidation of the chemical structures of the deposited films, as well as to the understanding of the nature of the sputtering process.…”
Section: Introductionmentioning
confidence: 99%
“…The great advantage of RF magnetron sputtering over commonly used plasma-enhanced chemical vapor deposition is the complete lack of gaseous or liquid precursors, which makes RF sputtering a “green” technology. Although much attention has been devoted to the fabrication and characterization of fluorocarbon plasma polymers [10,11,12,39,40,41,42,43,44,45,46,47], other polymers were also studied, including polyarylates [48], polyimides [45,49,50,51,52], polyethylene [50,53,54], polyetherimide [55], polypropylene [56,57], and Nylon [58].…”
Section: Introductionmentioning
confidence: 99%